Empowerment of Tribes, Informal Migrant Labor: A Study on Marginalized Groups - Nidasoshi, Vinayak R. (Current Progress in Arts and Social Studies Research Vol. 2, 2024)
Empowerment of tribes, informal migrant labors and marginalized groups in this study is a common issue in society. An empirical study to know how vulnerable groups are having programme's/schemes in India. India is one the sovereign countries in the world, all the categories, and all groups of people are living in one geographical or one environmental place called as a society. Where we all have equal opportunity to share and live in society. Empowerment tribal communities to reduce their poverty of exclusion by improving access to and monitoring of public services. The government on behalf of society, will provide programme's/schemes for individuals to live securely and the government will try to maintain equality among all. The relationship between government and society is in the form of a contract, with mutual collaboration in which society chooses the government and the government delivers schemes/programmes for the benefit of society.